DEVELOPING GREETING AND SELF INTRODUCING MATERIALS DEALING WITH 2013 CURRICULUM OF THE SEVENTH GRADE IN MTsN BALANG-BALANG - Hikmawati M; Djuwairiah Ahmad (Universitas Islam Negeri Alauddin Makassar, 2017)
Based on the preliminary study conducted in the MTsN Balang-Balang Gowa – Sulawesi, it is found that students demanded understandable materials to comprehend English subject as well as teachers faced several challenges in implementing the 2013 curriculum. In this regard, the complementary books are needed to complete the compulsory books provided by the government. Therefore, this study aims to develop a form of basic module and other references for teacher related to materials of greeting and self-introduction derived from 2013 curriculum. This study is Research and Development (R&D) adapted from ADDIE Model (Analysis, Design, Development, Implementation, and Evaluation) by Steve J. McGriff, 2000. The research procedure will start from analyzing materials in the syllabus of the 2013 Curriculum, analyzing the students’ need, designing the blueprint, developing the materials, implementing the materials in the classroom, and evaluating the materials by experts of 2013 Curriculum (evaluator students book) using experts’ judgment and rubrics of analyzing student book set by National Standard. The result of experts’ judgment and rubrics seems to be that the materials are good, well-designed, well-organized, and proper to use to the learners. It is also appropriate with the content of syllabus of the 2013 Curriculum and matches the students’ need.